2019
DOI: 10.1002/smll.201900299
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Correlated Aromatic Molecular Conductor

Abstract: Strongly correlated electronic molecules open the way for strong coupling between charge, spin, and lattice degrees of freedom to enable interdisciplinary fields, such as molecular electronic switches and plasmonics, spintronics, information storage, and superconducting circuits. However, despite exciting computational predictions and promising advantages to prepare flexible geometries, the electron correlation effect in molecules has been elusive. Here, the electron correlation effects of molecular plasmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Inspired by this feature, poly- p -phenylene (PPP), an organic phenyl system with a porous network structure composed of C and H, is also expected to be used as electrode materials for PIBs. The structures and fabrications of K-intercalated PPPs have been studied preliminarily. Previous studies showed that the K-intercalated PPP can be obtained by the solid-state reaction between pure potassium lumps and PPP sealed in glass tubes under high-vacuum conditions. , In this paper, therefore, we study K-intercalated PPP to examine the feasibility of PPP as the anode of PIBs, based on the first-principles calculations. Selected two typical systems of PPPs, biphenyl (C 12 H 10 ) and p -terphenyl (C 18 H 14 ), the K-intercalated structure, specific capacity, diffusion barrier, and electrical conductivity were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this feature, poly- p -phenylene (PPP), an organic phenyl system with a porous network structure composed of C and H, is also expected to be used as electrode materials for PIBs. The structures and fabrications of K-intercalated PPPs have been studied preliminarily. Previous studies showed that the K-intercalated PPP can be obtained by the solid-state reaction between pure potassium lumps and PPP sealed in glass tubes under high-vacuum conditions. , In this paper, therefore, we study K-intercalated PPP to examine the feasibility of PPP as the anode of PIBs, based on the first-principles calculations. Selected two typical systems of PPPs, biphenyl (C 12 H 10 ) and p -terphenyl (C 18 H 14 ), the K-intercalated structure, specific capacity, diffusion barrier, and electrical conductivity were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible electronics have demonstrated great potential in a wide range of wearable devices over the past decade. Electronic circuits have typically received little attention as a basic electronic component for transmitting electrical signals in wearable electronic devices. Traditional metal electronic circuits are made of rigid metal with low gauge factors, small strain ranges, and unsatisfactory wearing experiences, thus greatly limiting their implementation in wearable devices. Therefore, researchers have attempted to develop flexible electronic circuits to solve this problem, and various strategies have been proposed for fabricating such circuits.…”
Section: Introductionmentioning
confidence: 99%